2006
DOI: 10.1057/palgrave.jibs.8400195
|View full text |Cite
|
Sign up to set email alerts
|

Do domestic and foreign fund managers have similar preferences for stock characteristics? A cross-country analysis

Abstract: Using a new unique data set on mutual fund stockholdings, we identify several interesting similarities and differences in the stock preferences of domestic and foreign fund managers from 11 developed countries. Results show that both groups of managers prefer stocks with high return on equity, large turnover, and low return variability, and that they also exhibit differential investment behavior. Domestic managers also favor firms that pay large dividends, have low financial distress and high growth potential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
87
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 24 publications
17
87
1
Order By: Relevance
“…Since larger companies are more exposed to the public eye, take less time to report (Dyer & McHugh, 1975) and more information is available about them, foreign investors tend to have more knowledge about large companies than about small ones (Kang & Stulz, 1997). This leads to the expectation that less information asymmetry or lower cost of information acquisition will be found between domestic and foreign investors in large size companies (Covrig, Lau, & Ng, 2006). The larger the company size, the lower the information asymmetry degree (Kim & Yoo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since larger companies are more exposed to the public eye, take less time to report (Dyer & McHugh, 1975) and more information is available about them, foreign investors tend to have more knowledge about large companies than about small ones (Kang & Stulz, 1997). This leads to the expectation that less information asymmetry or lower cost of information acquisition will be found between domestic and foreign investors in large size companies (Covrig, Lau, & Ng, 2006). The larger the company size, the lower the information asymmetry degree (Kim & Yoo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…North-American investors also prefer companies with ADR and good corporate governance. Covrig et al (2006) have found results for preferences of mutual fund managers (foreign and domestic) from 11 developed countries. For both classes, liquidity and return on equity were significant.…”
Section: In Billions Of Dollarsmentioning
confidence: 99%
“…By selecting developed countries for the sample, Covrig et al (2006) tried to limit the surging of explicit barriers (the countries selected in their sample do not possess control capital politics) and limited it to those with more liquidity. Their results, however, were not different from the first ones, suggesting that the second class of implicit barriers (information asymmetry) has a bigger relevance.…”
Section: In Billions Of Dollarsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because illiquidity will substantially reduce the potential earnings in emerging markets. For this reason, foreign portfolio investors are more likely to prefer companies with higher liquidity (see Aggarwal et al, 2005;Chan et al, 2005;Covrig et al, 2006;Ferreira and Matos, 2008;and Rhee and Wang, 2009; among others). However, foreign investors, even if internationally well diversified, could still face foreign exchange risk exposure as their cross-currency exposures are not perfectly matched and canceled out.…”
Section: Liquiditymentioning
confidence: 99%